2008
DOI: 10.1136/adc.2007.131516
|View full text |Cite
|
Sign up to set email alerts
|

The implications of health literacy on patient-provider communication

Abstract: Limited health literacy has been associated with a range of adverse health outcomes including decreased use of preventive health services, poorer disease-specific outcomes for certain chronic conditions and increased risk of hospitalisation and mortality. Although the majority of research has been conducted in the adult population, there is a small and growing body of research on this subject in the paediatric literature. In this article, we will review the research on health literacy, consider the range of ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 44 publications
0
63
0
4
Order By: Relevance
“…Our taxonomy also discerns potential errors in events that others have conceptualized as causes of suboptimal health, such as memory lapses 20 and low health literacy. 21 Our patient groups were more willing than our groups of health care professionals to consider as potential mistakes the patient attitudes that are not conducive to health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our taxonomy also discerns potential errors in events that others have conceptualized as causes of suboptimal health, such as memory lapses 20 and low health literacy. 21 Our patient groups were more willing than our groups of health care professionals to consider as potential mistakes the patient attitudes that are not conducive to health.…”
Section: Discussionmentioning
confidence: 99%
“…13 Moreover, patients and their caregivers "make errors too." 14(p33) With some exceptions, [15][16][17][18][19] however, patients' contribution to their own suboptimal health 20,21 has not usually been conceptualized as error. Almost all the taxonomies of medical error, [4][5][6]8,9,22 do not discuss patients' contribution to error, or they acknowledge this contribution peripherally, 23 perhaps because patient error is a sensitive issue.…”
Section: Introductionmentioning
confidence: 99%
“…Specific healthcare provider communication strategies have been shown to improve communication and health outcomes [27,28] and previous research, mostly from the adult health literature, has demonstrated the positive impacts of providing patients with prompting questions, patient-communication training, strategies to improve information-seeking skills, and exposure to activation messaging [29][30][31][32][33]. This knowledge was used and integrated into the development of the training curriculum for WIC staff and the center-based education curriculum for WIC clients.…”
Section: Resultsmentioning
confidence: 99%
“…Even in the times of electronic medical records and telemedicine, parents of pediatric patients still expect that healthcare providers call them by their name and shake hands upon introductions [22]. Accordingly, the simple 'basic' techniques utilized in our pilot communication skills program should be promoted for all clinicians to use in their patient-provider interactions to ultimately improve health outcomes [6].…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy affects communication and interaction between patients and providers [2,6]. Poor communication pilot educational intervention on providers' knowledge and reported use of health literacy strategies; and 2) to describe participants' reasons to participate and their opinions regarding the educational intervention's delivery and content.…”
Section: Introductionmentioning
confidence: 99%